Vocational training of future elementary school teacher by means of realization of inter-subject continuity - G. Mailybaeva, S. Feizuldayeva, K. Ybyraimzhanov; Beisenbaeva, P. Ishanov, A.; Feizuldayeva, Saltanat (Opción, 2019)
The article considers the problem of high school training of future elementary school teacher by means of realization of inter-subject continuity. Scientific approaches of continuity in education are defined and its essence is revealed, which confirm the multidimensionality and universality of this concept. The structure of training of the elementary school teacher marks out the three basic components uniting the characteristics which are most closely connected with each other, acting as significant and steady structural formations at all historical stages of development of ideas about training of the teacher. There are determined such basic components as: knowledge, valuable and personal.